President Obama’s Marxist Mindset towards the Middle Class: 2010 to 2016 - Belarbi,Khadidja Anfal; Seddiki, Mohammed Cherif (Faculty of Letters and Foreign Languages Department of English, 2016)
This study is concerned with the field of American civilization. It is an attempt to explore Obama’s implementation of Marxism in his economic policies to serve the interest of the American middle class. This humble work tends to show how president Obama has exceptionally cared about the middle class which. Exploring a chain of events, or rather than decisions, could help getting an idea about how Obama’s economic policies work for the interest of the American middle class. And during my experience in this study, I came with the conclusion that Americans might be misunderstood Obama’s intentions towards them. He might be really caring for the middle class